(3eHGOF GdSGdcjf Edi ebGeGJ GdYGQajfs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO CjgG GdWGdH Ydi YJb QbHJg ef YbGH QHg hCdje YPGHg aYdjc HEeJKGd CeQg hfgjI ai eMce cJGHg aEPG MUdJ LejY eG JbOe PcQg aEf SQ GdYHGOI hQhMgG EfeG gh GdENdGU s
(3BNQgG (B:s
(3hGdMeO ddg GdPi gOGfG dgPG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hLejY CfHjGFg hedGFcJg hQSdg hGdMeO ddg QH GdYGdejf Je hced s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1578s
Keywords: (3GdJUha hGdBOGH GdTQYjIs